Genetic control of blast in relation to nitrogen fertilization in upland rice - Prabhu, Anne Sitarama; Filippi, Marta Cristina; Zimmermann, Francisco José P. (Pesquisa Agropecuaria Brasileira, 1996)
Six upland rice cultivars were evaluated under two nitrogen levels (10 kg and 60 kg N/ha) for blast control based on slow leaf and panicle blast characteristics in field experiments conducted during three consecutive years. The criteria for measuring slow blasting resistance were area under disease progress curve (AUDPC), maximum severity during disease progress (Ymax) and the rate of increase until the disease reaches maximum ('ymax). There was a high positive correlation among the criteria utilized. The control of leaf blast in improved rice cultivars (Cuiabaria, Centro América, Guarani, Rio Paranaíba) ranged from 36 to 56% for 10 kg/ha of N and from 19 to 49% for 60 kg/ha of N over the susceptible checks (IAC 47, IAC 165). The effect of slow blasting resistance on panicle blast control was less than on leaf blast in most of the cultivars. Increasing the nitrogen level from 10 to 60 kg/ha resulted in a mean yield increase by only 12% corresponding to 258 kg/ha. The data suggest that the existing level of slow blasting resistance in the improved rice cultivars is efficient only under low nitrogen level.
Keywords: resistance; Oryza sativa; Pyricularia grisea; Pyricularia oryzae; slow blasting; epidemiology